Calaxin is required for asymmetric bend initiation and propagation in sperm flagella - Shiba, Kogiku; Baba, Shoji A.; Fujiwara, Eiji; Inaba, Kazuo (Frontiers in Cell and Developmental Biology, 2023)
Regulation of waveform asymmetry in flagella is critical for changes in direction when sperm are swimming, as seen during the chemotaxis of sperm towards eggs. Ca2+ is an important regulator of asymmetry in flagellar waveforms. A calcium sensor protein, calaxin, is associated with the outer arm dynein and plays a key role in the regulation of flagellar motility in a Ca2+-dependent manner. However, the underlying mechanism of regulating asymmetric waves by means of Ca2+ and calaxin remains unclear. To clarify the calaxin-dependent mechanism for generating Ca2+-dependent asymmetric flagellar waveforms, we analyzed the initial step of flagellar bend formation and propagation in the sperm of the ascidian Ciona intestinalis. Our experiment used demembranated sperm cells, which were then reactivated by UV flash photolysis of caged ATP under both high and low Ca2+ concentrations. Here, we show that initial bends in the flagella are formed at the base of the sperm and propagate towards the tip during waveform generation. However, the direction of the initial bend differed between asymmetric and symmetric waves. When a calaxin inhibitor (repaglinide) was applied, it resulted in the failure of asymmetric wave formation and propagation. This was because repaglinide had no effect on initial bend formation, but it significantly inhibited the generation of the subsequent bend in the reverse direction. The mechanical transmission of microtubule sliding by dynein is crucial for flagellar oscillation. Our results suggest that the Ca2+/calaxin mechanism plays an important role in the switching of dynein activity from microtubule sliding in the principal bend into the suppressed sliding in the reverse bend, thereby allowing the sperm to successfully change direction.